Primary results of mechanical thrombectomy for acute ischemic stroke: The K-NET registry in the Japanese metropolitan area. Issue 5 (June 2023) - Ueda, Toshihiro; Hasegawa, Yasuhiro; Takeuchi, Masataka; Morimoto, Masafumi; Tsuboi, Yoshifumi; Yamamoto, Ryoo; Kaku, Shogo; Ayabe, Junichi; Akiyama, Takekazu; Ishima, Daisuke; Mori, Kentaro; Kagami, Hiroshi; et al.
Background: Endovascular treatment (EVT) for acute large vessel occlusion has proven to be effective in randomized controlled trials. We conducted a prospective cohort study to evaluate the real-world efficacy of EVT in a metropolitan area with a large number of comprehensive stroke centers and to compare it with the results of other registries and randomized controlled trials (RCTs). Methods: We analyzed the Kanagawa Intravenous and Endovascular Treatment of Acute Ischemic Stroke registry, a prospective, multicenter observational study of patients treated by EVT and/or intravenous tissue-type plasminogen activator (tPA). Of the 2488 patients enrolled from January 2018 to June 2020, 1764 patients treated with EVT were included. The primary outcome was a good outcome, which was defined as a modified Rankin Scale (mRS) of 0–2 at 90 days. Secondary analysis included predicting a good outcome using multivariate logistic regression analysis. Results: The median age was 77 years, and the median National Institute of Health Stroke Scale (NIHSS) score was 18. Pretreatment mRS score 0–2 was 87%, and direct transport was 92%. The rate of occlusion in anterior circulation was 90.3%. Successful recanalization was observed in 88.7%. The median time from onset to recanalization was 193 min. Good outcomes at 90 days were 43.3% in anterior circulation and 41.9% in posterior circulation. Overall mortality was 12.6%. Significant predictors for a good outcome were as follows: age, male, direct transfer, NIHSS score, Alberta Stroke Program Early Computed Tomography Score, intravenous tPA, and successful recanalization. Conclusion: EVT in routine clinical use in a metropolitan area showed comparable good outcomes and lower mortality compared to previous studies, despite the high proportion of patients with older age, pretreatment mRS score of >2, posterior circulation occlusion, and higher NIHSS. Those results may have been associated with more direct transport and faster onset-to-recanalization times.